Estimating overpressures in pole-type distribution transformers. I. Tank withstand evaluation. - Hamel, A. (IEEE Transactions on power delivery)
When an electric arc is generated in transformer oil, a strong overpressure may rapidly develop in the tank, especially for low-impedance faults. This paper presents the test method and results obtained in a project aimed at assessing the human and environmental risks associated with this type of fault. Limit energy and pressure values were defined in terms of different safety levels. The best method of limiting the energy and pressure at a safety level in the transformer tank during internal faults of greater than 1.7 kA is to protect the transformer with a current limiting fuse. Other ways to increase the mechanical withstand of transformer tanks under such faults are also discussed.